2001
DOI: 10.1038/90643
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cell effectors can become memory cells with high efficiency and without further division

Abstract: Whether memory T lymphocytes are derived directly from effector T cells or via a separately controlled pathway has long been debated. Here we present evidence that, after adoptive transfer, a large fraction of in vitro--derived effector CD4(+) T cells have the potential to become memory T cells and that this transition can occur without further division. This data supports a linear pathway from effector to memory cells and suggests that most properties of memory cells are predetermined during effector generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
172
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 45 publications
8
172
0
Order By: Relevance
“…One possibility is that persistence of a peptide on the class II molecule provides an advantage for stable CD4 memory generation and maintenance. Although it is known that antigen persistence is not required to generate memory cells (42)(43)(44)(45), it is possible that continued opportunities to engage the CD4 T cells agonist ligand provides some advantage in the quantity or quality of memory T cells (29,(46)(47)(48)(49). Also, engagement of CD4 T cells, particularly follicular helper T cells, with antigen-specific B cells in the germinal center may be most efficient and long-lived for stable peptide:class II complexes (23).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that persistence of a peptide on the class II molecule provides an advantage for stable CD4 memory generation and maintenance. Although it is known that antigen persistence is not required to generate memory cells (42)(43)(44)(45), it is possible that continued opportunities to engage the CD4 T cells agonist ligand provides some advantage in the quantity or quality of memory T cells (29,(46)(47)(48)(49). Also, engagement of CD4 T cells, particularly follicular helper T cells, with antigen-specific B cells in the germinal center may be most efficient and long-lived for stable peptide:class II complexes (23).…”
Section: Discussionmentioning
confidence: 99%
“…Cells that produce IFN-␥ are by definition effector memory cells (33), whereas cells that produce IL-2 would include three subsets consisting of naive cells, effector memory cells (33), as well as Ag-experienced effector cells that have returned to a resting state (44). The selective reduction in the number of double-positive effector cells may be a consequence of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of Effectors, Rested Effectors, and Memory CellsTh1 and Th2 effectors and rested effectors were generated as described previously (15,17). Highly purified naïve cells (1.5 ϫ 10 5 /ml) from AND TCR Tg mice were cultured with mitomycin C (100 g/ml)-treated fibroblast APC expressing B7 and ICAM-1 (DECK.ICAM) (7.5 ϫ 10 4 /ml) and 5 M pigeon cytochrome c fragment, amino acids 88 -104 (PCCF).…”
Section: Methodsmentioning
confidence: 99%
“…We found that when in vitro generated CD4 ϩ T cell effectors are further cultured in the absence of antigenic stimulation, they revert to a resting state that phenotypically resembles memory cells (16,17). When we adoptively transferred these "rested effector" cells, they migrated mainly to lymphoid sites and efficiently developed into long lived memory cells, which persist indefinitely without the need for any further division (17). This raises the possibility that recruitment to non-lymphoid sites is restricted to highly activated effectors.…”
mentioning
confidence: 99%